Impactos da relação professor-aluno na aprendizagem - Amaral, Letícia da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This work discusses issues related to teacher-student affection and how this relationship impacts on learning. A qualitative research was carried out, in which the main objective sought to understand and discuss the importance of affectivity in the teacher-student relationship and its impact on learning, in a literature review. We also seek to identify the importance of affectivity in human relationships. Describe the role of the educator in the learning process based on the researched literature and analyze how positive affective relationships between teacher-students interfere in the learning process. As a methodological procedure, a literature review was carried out on the Scielo platform. The organization and analysis of the contents were carried out according to the methodology recommended by Bardin. Six articles were selected with the survey, categorizing them as: “importance of affectivity in human relationships”, “the role of the educator in the learning process” and “how affective relationships interfere in the learning process”. It can be concluded that affection is something important that should be present in human relationships in the school environment, as affection is a very positive tool that can help in the teaching-learning process. Despite being so important, it is often not seen as something important in the school environment.

Esse trabalho discute questões relativas à afetividade professor-aluno e, como esse relacionamento impacta na aprendizagem. Foi realizada uma pesquisa qualitativa, em que o objetivo principal buscou compreender e discutir a importância da afetividade na relação professor-aluno e seu impacto na aprendizagem, em uma revisão de literatura. Buscamos também identificar a importância da afetividade nas relações humanas. Descrever o papel do educador no processo de aprendizagem a partir da literatura pesquisada e analisar como relações afetivas positivas entre professor-aluno interferem no processo de aprendizagem. Como procedimento metodológico, foi realizada uma revisão bibliográfica na plataforma Scielo. A organização e análise dos conteúdos foram realizadas conforme a metodologia preconizada por Bardin. Com o levantamento foram selecionados seis artigos, categorizando–os em: “importância da afetividade nas relações humanas”, “papel do educador no processo de aprendizagem” e “como as relações afetivas interferem no processo de aprendizagem”. Pode-se concluir que a afetividade é algo importante que deveria estar presente nas relações humanas do ambiente escolar, pois o afeto é uma ferramenta muito positiva que pode auxiliar no processo de ensino aprendizagem. Apesar de ser tão importante, muitas das vezes não é visto como algo importante no ambiente escolar.
Impacts of the teacher-student relationship on apprenticeship
Keywords: Affection; Teaching and learning process; Teacher-student relationship; Afetividade; Processo de ensino e aprendizagem; Relação professor-aluno